Citrus aurantium (bitter orange) seeds oil: pharmacognostic, anti-inflammatory and anti-nociceptive properties - Azadeh Hamedi; Mohammad M. Zarshenas; Akram Jamshidzadeh; Saeed Ahmadi; Reza Heidari; Ardalan Pasdaran (Shiraz University of Medical Sciences, 2019)
The present investigation was carried out to evaluate the pharmacognostic properties of Citrus aurantium seeds as well as its anti-inflammatory activities. The n-hexane fraction of seed oil extracted via a Soxhlet extractor and subjected to pharmacognostic assays, HPTLC and GC-MS analysis for determination of fatty acids and sterols. The possible anti-inflammatory and antinociceptive activities in rats were evaluated using formalin-induced paw licking, oedema and myeloperoxidase activity assessment. Total ash, acid insoluble and water soluble ash values were determined as 35.83 ± 4.92, 6.67 ± 2.89 and 28.33 ± 5.77 mg/g, respectively. HPTLC assessment revealed the presence of different fatty acids and steroidal triterpenes. The principal fatty acids of the seed oil were linoleic acid (C18:2, 50.10 ± 2.58 %) and Oleic acid (C18:1, 30.14 ± 0.39). Esterified (2.40 mg/g) and free β-sitosterol (32.90 mg/g), free campesterol (3.9 mg/g) and free stigmasterol (10.165 mg/g) were detected in the oil. Seed oil exhibited anti-inflammatory properties in the first and the second phases of formalin test. Also, it had anti-edematogenic effects but exerted no effects on myeloperoxidase activity.